PENGARUH MEDIA PROMOSI DAN KUALITAS PELAYANAN TERHADAP MINAT MENABUNG MASYARAKAT DI BANK SYARIAH - Salsabila Putri Damayanti; Norma Rosyidah (STAI AN-NAJAH INDONESIA MANDIRI, 2022)
To increase public knowledge regarding sharia banking information through promotional media both through print and internet media and the quality of services that play an active role. The better and more knowledge about Islamic banks through promotional media that is spread and the quality of good service to the community, the higher the possibility of using Islamic banks. The purpose of this study was to determine the influence of promotional media and service quality on people's interest in saving in Islamic banks. This research uses quantitative methods. The data used in this research is primary data. Primary data was obtained from questionnaires distributed to 40 customers in Islamic banks. By using reliability test, validity test, T test, and F test. Data analysis used multiple linear regression and the results showed that promotional media had no significant effect on people's interest in saving in Islamic banks and service quality did not significantly influence people's interest in saving in Islamic banks . Keywords : Promotional Media, Quality of Service, Public Interest in Saving References Arief Firdy Firmansyah 2019.